Analisa Permintaan Pangan: Bukti Empiris Teori Rumah Tangga Pertanian - M. Husein Sawit (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1994)
Most of demand parameters of rural households in Indonesia estimated by applying conventional neo-classical demand model. This model is not appropriate to predict the complex nature of rural household consumption decisions. The complex nature of rural household's production and consumption decisions was approached in this study by applying the farm household model. In this study two hundred and forty-one households in six villages of the Cimanuk River Basin of West Java were analysed. Results from the conventional model and new model were compared and discussed.